Clinical Utility of the Parent-Report Version of the Strengths and Difficulties Questionnaire (SDQ) in Latvian Child and Adolescent Psychiatry Practice - Ņikita Bezborodovs; Arta Kočāne; Elmārs Rancāns; Anita Villeruša (Medicina, 2022)
Background and Objectives: Screening instruments can be crucial in child and adolescent mental healthcare practice by allowing professionals to triage the patient flow in a limited resource setting and help in clinical decision making. Our study aimed to examine whether the Strengths and Difficulties Questionnaire (SDQ), with the application of the original UK-based scoring algorithm, can reliably detect children and adolescents with different mental disorders in a clinical population sample. Materials and Methods: a total of 363 outpatients aged 2 to 17 years from two outpatient child psychiatry centres in Latvia were screened with the parent-report version of the SDQ and assigned clinical psychiatric diagnoses. The ability of the SDQ to predict the clinical diagnosis in major diagnostic groups (emotional, conduct, hyperactivity, and developmental disorders) was assessed. Results: The subscales of the parent-report SDQ showed a significant correlation with the corresponding clinical diagnoses. The sensitivity of the SDQ ranged 65–78%, and the specificity was 57–78%. The discriminative ability of the SDQ, as measured by the diagnostic odds ratio, did not quite reach the level of clinical utility in specialised psychiatric settings. Conclusions: We suggest the SDQ be used in primary healthcare settings, where it can be an essential tool to help family physicians recognise children needing further specialised psychiatric evaluation. There is a need to assess the psychometric properties and validate the SDQ in a larger populational sample in Latvia, determine the population-specific cut-off scores, and reassess the performance of the scale in primary healthcare practice.